The Effectiveness of Articulate Storyline 3-Based Learning Media on Students’ Learning Outcomes in Inorganic Compound Nomenclature - Motuhonu, Yulius Bagara; Enawaty, Eny; Sahputra, Rachmat (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The use of technology-based learning media is still rarely applied by chemistry teachers in schools, teachers tend to use conventional methods such as lectures and assignments, so that student learning outcomes are still low, one of the learning media that can be applied is Articulate Storyline 3. The purpose of this study was to determine the effectiveness of using Articulate Storyline 3-based learning media on the material of Nomenclature of Inorganic Compounds. The method used is Quasi Experimental Nonequivalent Control Group Design. With a sample of class XI-F5 as the experimental class and XI-F4 as the control class, each with 32 students. The results of the normality test showed that some of the data were not normally distributed, and the homogeneity test showed that the posttest variance was not homogeneous (Sig. = 0.040 <0.05), so the Mann-Whitney U test was used, the test results showed a significant difference between the pretest and posttest scores in the experimental class with a value of (0.001 <0.05). Then the effect size value was obtained at 0.915 with a large category. Thus, the use of learning media based on Articulate Storyline 3 is more effective in improving students’ learning outcomes in the material on nomenclature of inorganic compounds.